Pengaruh Lama Steam Blanching dan Metode Pengeringan Terhadap Warna, Β-Karoten, Serta Serat Kasar Bubuk Temulawak (Curcuma Xanthorrhiza Roxb.) - Bella Farhanah Sasandira; Dwiyati Pujimulyani; Bayu Kanetro (Journal of Food and Agricultural Technology, 2025)
Javanese turmeric (Curcuma xanthorrhiza Roxb.) is a rhizome plant widely used as a functional food ingredient and in traditional medicine due to its bioactive compounds. The content of these bioactive compounds is significantly influenced by processing methods, particularly pretreatment and drying methods. This study aims to determine the effects of steam blanching duration and drying methods on the color, β-carotene content, and crude fiber content of temulawak powder. The study employed a factorial Complete Randomized Design (CRD) with two factors: steam blanching duration (0; 2.5; 5; 7.5; and 10 minutes) and drying method (sun-drying and cabinet dryer). Data were analyzed using Analysis of Variance (ANOVA) at a 95% confidence level, followed by Duncan’s multiple range test if significant differences were found. The results showed that the duration of steam blanching had a significant effect on the moisture content, color, β-carotene, and crude fiber of the temulawak powder. The treatment of 2.5 minutes of steam blanching combined with sun-drying produced the highest β-carotene content of 114.67 µg/g and the highest crude fiber content of 3.24%.